Malignancy in Membranous Nephropathy: Evaluation of Incidence. (16th July 2017) - Alnasrallah, Basil; Collins, John F.; Zwi, L. Jonathan
Abstract : Background . Membranous nephropathy (MN) can be associated with malignancy. However, the relative risk for malignancy remains unclear. It has been reported that higher numbers of inflammatory cells seen in the glomeruli at biopsy correlate with the occurrence of malignancy in patients with MN and might be used to direct screening. Methods . We examined the occurrence of malignancy in 201 MN patients in Auckland, New Zealand. We also examined the pathology of renal biopsies from 17 MN patients with malignancies and compared the number of inflammatory cells per glomerulus with matched control patients with MN but no malignancy. Results . 40 malignancies were identified in 37 patients, 28 of which occurred after the MN diagnosis. The standardized incidence ratio (SIR) was 2.1 (95% CI, 1.3–2.85) which was similar between patients ≥ 60 years and those <60 years. The median number of inflammatory cells per glomerulus did not differ between MN patients with and without malignancy at 1.86 (IQR, 1.17–2.7) and 2.07 (IQR, 1.17–3.65), respectively ( p value 0.56). Conclusions . The relative risk of malignancy in MN patients was similar across different age groups. The number of inflammatory cells per glomerulus did not differentiate between MN patients with and without malignancies.